2006
DOI: 10.1007/s11418-006-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated flavonoids and related compounds of the Indonesian Artocarpus (Moraceae)

Abstract: Several species of the genus Artocarpus (Moraceae) have been investigated in our laboratories during the last decade. Over 60 phenolic constituents have been discovered and characterized, including 27 new compounds from 13 Indonesian taxa of Artocarpus, namely A. champeden, A. lanceifolius, A. teysmanii, A. scortechinii, A. rotunda, A. maingayi, A. kemando, A. bracteata, A. altilis, A. fretessi, A. gomezianus, A. reticulatus and A. glaucus. The principal and the most pronounced features of these phenolic const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 50 publications
2
50
0
3
Order By: Relevance
“…The cytotoxic effects of the three isolated compounds 1-3 against the P-388 murine leukimia cells were conducted according to the method described in previous paper [19,20] and were used an artonin E (IC 50 0.3 μg/mL) as a positive control [21]. Compounds 1-3 showed cytotoxicity against P-388 murine leukimia cells with IC 50 values of 51.8, 100 and 3.32 μg/mL, respectively, suggested that the presence of rhamnoside sugar unit in flavonoid structure can increase cytotoxic activity whereas the presence of glucoside unit can decrease cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic effects of the three isolated compounds 1-3 against the P-388 murine leukimia cells were conducted according to the method described in previous paper [19,20] and were used an artonin E (IC 50 0.3 μg/mL) as a positive control [21]. Compounds 1-3 showed cytotoxicity against P-388 murine leukimia cells with IC 50 values of 51.8, 100 and 3.32 μg/mL, respectively, suggested that the presence of rhamnoside sugar unit in flavonoid structure can increase cytotoxic activity whereas the presence of glucoside unit can decrease cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity values of the four isolated compounds 1-4 against the P388 murine leukemia cells were conducted based on experiment in previous paper [8,24,25] and artonin E (IC50 0.75 µg/mL) used as a positive control [26].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Selain itu artoindonesianin E (3) ditemukan pula dari kulit batang A. champeden [10]. Senyawa flavanon terprenilasi pada posisi C-6 atau C-8 telah diisolasi dari akar dan buah A. heterophyllus yaitu heteroflavanone C (4) [11].…”
Section: Pendahuluanunclassified
“…Secara biogenesis, senyawa oksepinoflavon dapat berasal dari senyawa 2',4'-dioksigenasi atau 2',4',5'-trioksigenasi 3-prenilflavon (sebagai prekursor), melalui reaksi siklisasi oksidatif yang melibatkan pembentukan ikatan -C-O-C-antara gugus OH pada C-2' dengan C-10 dari gugus isopren pada C-3. Senyawa caplasin (21) merupakan senyawa pertama dari golongan oksepinoflavon yang berhasil diisolasi dari Artocarpus, yaitu dari A. maingayii [10]. Selain itu, artoindonesianin B (22) merupakan senyawa golongan oksepinoflavon yang berhasil diisolasi dan dikarakterisasi dari A. champeden [14].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation